2020
DOI: 10.1007/s10606-020-09376-y
|View full text |Cite
|
Sign up to set email alerts
|

Coding and Classifying Knowledge Exchange on Social Media: a Comparative Analysis of the #Twitterstorians and AskHistorians Communities

Abstract: As social media become a staple for knowledge discovery and sharing, questions arise about how self-organizing communities manage learning outside the domain of organized, authority-led institutions. Yet examination of such communities is challenged by the quantity of posts and variety of media now used for learning. This paper addresses the challenges of identifying (1) what information, communication, and discursive practices support successful online communities, (2) whether such practices are similar on Tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 67 publications
0
5
0
4
Order By: Relevance
“…Analysis of Reddit data to get insights into professional communities is getting popular among scholars (Gilbert, 2020; Gruzd et al , 2020). The studies demonstrated that these communities offer their members a space for in-depth conversations and receiving advice.…”
Section: Methodsmentioning
confidence: 99%
“…Analysis of Reddit data to get insights into professional communities is getting popular among scholars (Gilbert, 2020; Gruzd et al , 2020). The studies demonstrated that these communities offer their members a space for in-depth conversations and receiving advice.…”
Section: Methodsmentioning
confidence: 99%
“…Os ambientes informais não foram inicialmente projetados para fins de ensino e aprendizagem. Eles surgiram com o advento da Internet, se popularizaram rapidamente com a Web 2.0 e atualmente são utilizados por estudantes e profissionais para a execução de atividades colaborativas, o que tem levado pesquisadores a investigar sua utilização como contextos em que a aprendizagem acontece de forma espontânea (GREENHOW; GIBBINS; MENZER, 2015;GRUZD et al, 2020;DERNTL;KLAMMA, 2015). Contudo, grande parte dos estudos em educação online e LA possuem como objetivo investigar os ambientes formais de aprendizagem, como os LMS ou os MOOC, em que o processo educativo acontece predominantemente de forma roteirizada.…”
Section: Motivaçãounclassified
“…Contudo, grande parte dos estudos em educação online e LA possuem como objetivo investigar os ambientes formais de aprendizagem, como os LMS ou os MOOC, em que o processo educativo acontece predominantemente de forma roteirizada. Este cenário faz com que os ambientes informais permaneçam sub-representados na pesquisa em aprendizagem online, mesmo considerando a sua onipresença em contextos pedagógicos (NISTOR; DERNTL; KLAMMA, 2015;GRUZD et al, 2020;HUDGINS et al, 2020).…”
Section: Motivaçãounclassified
See 2 more Smart Citations